ANALISIS KONSEP GREEN PRODUCT SEBAGAI PELAKSANAAN ETIKA BISNIS PADA PERUSAHAAN - Ida Hendarsih (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
Green Product not just produce goods and services but involves all aspects of business activities started production processes, product offer and distribution of environmentally friendly products to consumers. Activity-based business environment, a new development in the production of goods and services, is a potential and strategic opportunities that have the double advantage (multiplier effect) both businesses and the community. This discussion aims to assess the application of the concept of green product that is closely related to business ethics, that every business activity must preserve the environment, has a concern for the environment, by applying environmental impact assessment, as the law requires environmental impact assessment (EIA) and the granting ecolabel label on every product in accordance with ISO14020 and ISO14024 standards. Assessment using a qualitative approach and examine the implementation of green management is done according to the law firm business ethics. From the results of studies in recent decades many companies are already implementing green product in productivity activities. The stakeholders have awareness of business ethics implement one consciousness produce environmentally friendly and healthy products. Moral motive that individual businesses can be the motor of the application of ethics in a business organization. Keywords: Green Product, business ethics